Framing 'China' in Malaysian political sphere: a content analysis of China related reports during the 2018 election of The Star - Kuan, Duan; Mohd Hasan, Nurul Ain (Asian Scholars Network, 2021)
Political change events play a significant role in drawing media coverage and, by extension, impact on international public relations. This paper aims to explore how Malaysian media outlet The Star frames China’s national image during the major political change in 2018 by drawing upon framing theory. This study provides insight on the effects of Malaysian mega political change on the reported national image of a stakeholder country. Practical and theoretical implications are discussed and future research directions are provided.